Antiretroviral treatment programmes in Nepal: Problems and barriers - Wasti, SP; Simkhada, P; Van Teijlingen, ER (Kathmandu University Medical Journal, 2010)
Background: Antiretroviral (ARV) drugs have become the cornerstone of HIV (Human Immunodeficiency Virus) care and treatment. Its use has led to a marked reduction in AIDS (Acquired Immune Deficiency Syndrome) related morbidity and mortality. However, more than five years after their introduction few HIV infected people in Nepal are receiving ARVs. Objective: The main aim of this study is to identify barriers and obstacles to providing and expanding ARV programmes in Nepal. Materials and methods: A qualitative approach consisting of in-depth interviews with three groups of stakeholders: policy makers, ARV service providers and ARV recipients were carried out. The transcripts were analysed using a thematic approach. Results: The estimated number of people in need was high compared with people currently receiving ARV in Nepal. With regards to the proper distribution of the ARVs, the main problems identified in the interviews were: lack of infrastructure, lack of human resources, financial constraints, programmatic problems, weak leadership and management at national level, poor cooperation between management structures, geographical barriers, lack of awareness and low uptake of counselling and/or testing, stigmatization and discrimination felt by the health workers and the community, lack of coordination and limited access to services. Conclusion: Limited resources and administrative capacity coupled with strong underlying needs for services pose serious challenges to the government. Despite this, better use could be made of existing services and resources to help benefit more people from ARV. Key words: Service provision; Antiretroviral Treatment; HIV/AIDS; Programme Management DOI: 10.3126/kumj.v7i3.2743 Kathmandu University Medical Journal (2009) Vol.7, No.3 Issue 27, 306-314